Prediction of queue length due to lane closure with shockwave analysis on Jagorawi toll road (case study: Km 19+600) - Widjajanti, Endang (Edelweiss Applied Science and Technology, 2024)
This study discusses the prediction of queue length with shockwave analysis through traffic flow characteristics on the Jagorawi toll road KM 19+600. The purpose of this study is to analyze the relationship between traffic characteristics (current, density and speed) on the Jagorawi KM19+600 toll road and evaluate the value of shock waves due to the narrowing of the road on the Jagorawi KM 19+600 toll road when the lane is closed. The method used to achieve the purpose of this study is to use the linear regression method to determine the relationship between traffic variables through the Greenshield model. The data obtained was obtained from CCTV data recording at KM 19 + 600. The results of the current-velocity-density relationship analysis show that the selected model for the relationship is the Greenshield model with a maximum current of 9574 pcu/hour. From the results of the shock wave simulation for the closure of 1 lane, 2 lanes and 3 lanes with the same flow, namely 7200 pcu/hour. It can be known the length of the queue that occurs, where the length of the queue that occurs depends on the volume of traffic, the length of the closure and the number of lanes that are closed.